2017
DOI: 10.1051/0004-6361/201730490
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical adjustments in IAU 2000A nutation series arising from IAU 2006 precession

Abstract: The adoption of International Astronomical Union (IAU) 2006 precession model, IAU 2006 precession, requires IAU 2000A nutation to be adjusted to ensure compatibility between both theories. This consists of adding small terms to some nutation amplitudes relevant at the microarcsecond level. Those contributions were derived in previously published articles and are incorporated into current astronomical standards. They are due to the estimation process of nutation amplitudes by Very Long Baseline Interferometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
(72 reference statements)
0
18
0
Order By: Relevance
“…The computation of this effect (Escapa et al 2014(Escapa et al , 2015, following the perturbation equations, leads to the appearance of mixed secular terms (proportional to t, previously reported in Capitaine et al 2005), and to in-and out-of-phase nutations. Namely, the following expressions to be summed to equations (3) are 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 obtained…”
Section: On Ggos the Global Geodetic Observingmentioning
confidence: 94%
See 2 more Smart Citations
“…The computation of this effect (Escapa et al 2014(Escapa et al , 2015, following the perturbation equations, leads to the appearance of mixed secular terms (proportional to t, previously reported in Capitaine et al 2005), and to in-and out-of-phase nutations. Namely, the following expressions to be summed to equations (3) are 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 obtained…”
Section: On Ggos the Global Geodetic Observingmentioning
confidence: 94%
“…To be consistent in the development of the theory, the inclusion of the J 2 time rate forces the consideration of the time rate of the orbital coefficients A (0,1,2) i (Kinoshita 1977), due to the secular variation of Sun eccentricity (Escapa et al 2014(Escapa et al , 2015. Analytically its treatment is similar to that of J 2 rate, providing also out-of-phase nutations and mixed secular terms with formulas similar to equations (10).…”
Section: On Ggos the Global Geodetic Observingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the WG in charge considered that nutations were out of the scope of its task, and the fact was not mentioned in the IAU resolution. Later, Escapa et al (2014Escapa et al ( , 2016Escapa et al ( , 2017 showed that a few additional terms of the same order of magnitude have to be added to the 2005 expressions to get complete dynamical consistency between the official precession and nutation models. The issue was discussed in several occasions, particularly inside the IAU/ International Association of Geodesy (IAG) Joint Working Group on Theory of Earth rotation and validation (JWG TERV), and the main authors were invited to propose actions.…”
Section: Introductionmentioning
confidence: 99%
“…The latter amplitudes are implicitly factorized by J 2 through H d or the K S;M Kinoshita's constants (Kinoshita and Souchay 1990), and besides they depend on several circular functions of the 0 obliquity. Therefore, the total induced variations of the non-rigid Earth amplitudes cannot be got by simply making a rescaling associated only to J 2 (Escapa et al 2014(Escapa et al , 2016(Escapa et al , 2017Escapa and Capitaine 2018a,b).…”
Section: Introductionmentioning
confidence: 99%